Structure-transport relationships in disordered solids using integrated rate of gas sorption and mercury porosimetry - Nepryahin, Artjom; Holt, Elizabeth M.; Fletcher, Rob S.; Rigby, Sean P. (Elsevier, 2016)
This work describes a new experimental approach that delivers novel information on structure-transport relationships in disordered porous pellets. Integrated rate of adsorption and mercury porosimetry experiments have been used to probe the relative importance of particular sub-sets of pores to mass transport rates within the network of two disordered porous solids. This was achieved by examining the relative rates of low pressure gas uptake into a network, both before, and after, a known set of pores was filled with frozen, entrapped mercury. For catalyst pellets, formed by tableting, it has been found that the compaction pressure affects the relative contribution to overall mass transport made by the subset of the largest pores. Computerised X-ray tomography (CXT) has been used to map the spatial distribution of entrapped mercury and revealed that the relative importance of the sub-sets of pores is related to their level of pervasiveness across the pellet, and whether they percolate to the centre of the pellet. It has been shown that a combination of integrated mercury porosimetry and gas sorption, together with CXT, can comprehensively reveal the impact of manufacturing process parameters on pellet structure and mass transport properties. Hence, the new method can be used in the design and optimisation of pellet manufacturing processes.